PENGARUH MOTIVASI, PENGALAMAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA GURU M - Nurul Hasanah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
This Research isconducted on the basis of assumption that teacher performance influenced by motivation, job experience and satisfaction of teacher activity. This research aim to to know what is motivation, job experience and satisfaction of teacher activity have an effect on by signifikan to performance learn in Madrasah Ibtidayah Banjang and to know what is motivation, job experience and satisfaction of activity do not have an effect on by signifikan to satisfaction of activity learn in Madrasah Ibtidayah Banjang, by using quantitative research method. Result of research of that Variables Motivation, Job Experience and Satisfaction of activity by self or parsial there is having an effect on signifikan and there is which do not have an effect on signifikan to performance Learn MI Banjang. From third Variables Motivation, job experience of Satisfaction of activity hence variable satisfaction of activity represent variable owning dominant influence to performance Learn MI Banjang.Keyword : motivation, job experience, satisfaction of activity and performance.